If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -5(4 + -3x) = 4(x + -92) + 108 3 + (4 * -5 + -3x * -5) = 4(x + -92) + 108 3 + (-20 + 15x) = 4(x + -92) + 108 Combine like terms: 3 + -20 = -17 -17 + 15x = 4(x + -92) + 108 Reorder the terms: -17 + 15x = 4(-92 + x) + 108 -17 + 15x = (-92 * 4 + x * 4) + 108 -17 + 15x = (-368 + 4x) + 108 Reorder the terms: -17 + 15x = -368 + 108 + 4x Combine like terms: -368 + 108 = -260 -17 + 15x = -260 + 4x Solving -17 + 15x = -260 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -17 + 15x + -4x = -260 + 4x + -4x Combine like terms: 15x + -4x = 11x -17 + 11x = -260 + 4x + -4x Combine like terms: 4x + -4x = 0 -17 + 11x = -260 + 0 -17 + 11x = -260 Add '17' to each side of the equation. -17 + 17 + 11x = -260 + 17 Combine like terms: -17 + 17 = 0 0 + 11x = -260 + 17 11x = -260 + 17 Combine like terms: -260 + 17 = -243 11x = -243 Divide each side by '11'. x = -22.09090909 Simplifying x = -22.09090909
| 3+x+5=8 | | x+(x*.88)=10000000 | | 8(y+2)= | | 75x-3(5-3x)=100x-30 | | 4/9-1/2 | | -16=8x+16 | | -8x+3(x-8)=-4 | | (x-6)-[3-(2x-7)+x]=0 | | 3x(15)=56x | | 3x(15)=45x | | 7/9x+36=5/x+4-2/9 | | 10-(2y-1)=5-3y | | 4[2x-3]=3+8x-11 | | 1.2(2x-1)=2.7x+0.3 | | -6+4+14y=32 | | [0.1+0.05(20)]=[0.09(20)] | | 5x^2+20-60=0 | | 3x-3=7x-14 | | 3/4(2x-7)+1/2x=-9 | | 3x^2+24x+21= | | 2(5x+4)=3x-10 | | 12+-4=8 | | 6/x-2=(-5/x+5)+(9/(x-2)*(x+5)) | | 0.5y+2=0.8y+-0.3y | | 5x^2+21x-54=0 | | 8-(4n-7)=4-5n | | -24=4(2+2x) | | 3.14*x=9 | | -17=3+2(f+5) | | -4(z+7)-(-2z-9)=-3z | | 2+6c=-20 | | 9a-12=24 |